Wybrana. O powieści Ewy Stachniak „Bogini tańca” - Zatorska, Matylda (Wydawnictwo Uniwersytetu Rzeszowskiego, 2018)
The article is review on the latest book by Ewa Stachniak, “The Chosen Maiden”. It is a fictionalised biography belonging to more and more popular feminocentric trend of the contemporary historical fiction. Stachniak based on the life of ballet dancer-choreographer Bronislawa Nijinska, sister of Vaslav Nijinsky. Having done much research, she convincingly articulates what she imagines to be the workings of Bronia’s mind, her passion and conviction as an artist, and her ability to endure privates tragedies.
“The Chosen Maiden”. About the novel by Ewa Stachniak
Keywords: Ewa Stachniak; Bronisława Niżyńska; the novel about female artist; historical novel; herstory; powieść o artystce; powieść historyczna